Interpretation of GPR Field Data by Using Forward Modeling - ., Arisona; Mohd Noordin, Mohd Nawawi; J, Safani; Safiuddin, L.O. (International Journal of Science, Engineering, and Sustainable Technology (IJSESTech), 2014)
The forwad modeling using the Reflex software of ground penetrating radar (GPR) to minimize misinterpretation in the identification of subsurface material GPR data has been carried out. The misinterpretation may be caused by the multple and noise due to non-ideal condition of materials beneath the Earth surface. By forwad modeling, the multiple and noise can be reduced, that is by taking the dominant material as homogeneous or ideal condition. A profile/cross section model of the soil layer, the absorption properties of electromagnetic waves, is considered. The result showed that the response given through the forward modeling approached the lithology form of gold quartz vein with a slope of 600. Comparison to a field model shows a good accuracy of the forward modeling.